Effect of Surface-activated PLLA Scaffold on Apatite Formation in Simulated Body Fluid - Park, Kwideok; Jung, Hyun Jung; Kim, Jae-Jin; Han, Dong Keun (SAGE PUBLICATIONS LTD, 2010)
Surface-activated poly(L-lactic acid) (PLLA) films and scaffolds were investigated for their effect on the formation of hydroxyapatite (HA) in simulated body fluid (SBF). PLLA samples were treated with plasma discharge in oxygen gas; the activated polymer surfaces were subjected to in situ grafting acrylic acid (AA) monomer. The obtained PLLA-PAA was converted to PLLA-PAA-HA in SBF. The formation of HA crystals was identified by surface analyses and the size and distribution by scanning electron miscroscopy. The major elements of HA surface-modified PLLA were confirmed by electron spectroscopy for chemical analysis and attenuated total reflectance-Fourier transform infrared spectra. Fibroblast, chondrocyte, and osteoblast cells were seeded in scaffolds and cultivated in vitro; the total cellularity was higher in the PLLA-PAA-HA scaffolds than the PLLA and PLLA-HA. Histological staining of the cells was denser in the cell-seeded PLLA-PAA-HA constructs. The introduction of specific functionality on the polymer surface significantly improved apatite nucleation and growth. Thus, HA-formed PLLA scaffolds are potentially useful in musculoskeletal tissue engineering.
Keywords: COMPOSITE SCAFFOLDS; PROTEIN ADSORPTION; ORGANIC POLYMERS; SERUM-PROTEINS; BONE; HYDROXYAPATITE; ADHESION; CELLS